DINAMIKA EKOWISATA TRI NING TRI DI BALI PROBLEMATIKA DAN STRATEGI PENGEMBANGAN TIGA TIPE EKOWISATA BALI - I Nyoman Sukma Arida (Jurnal Kawistara, 2014)
This study is aimed at explain the dynamic process in the development of ecotourism in Bali. Its objectivesare 1) to identify and analyze typologies of ecotourism in Bali, 2) to analyze each type of ecotourism, focusingon the aspects of ecotourism products, local community involvement, and its development strategy, and 3) toanalyze and formulate appropriate model of ecotourism development in Bali. This is a descritive qualitativeresearch with relevant data acquisition techniques, namely (a) in-depth interview, (b) field observation,(c) Focus Group Discussion(FGD), and (d) document studies. The four methods were used to capture theneeds of data in the field, in accordance with scope of the problem investigated and research objectives. Thisstudy found that ecotourism typology in Bali, in terms of its main moving actors (agent of change),is divided into three, namely: (1) investor-driven ecotourism (investor type), (2) community-drivenecotourism (community type), and (3) government-driven ecotourism (government type). This threetypeecotourism in Bali is also known as tri ning tri. In practice, each type of ecotourism has different levelof conformity with ecotourism principles (TIES, 2000), so that they can be categorized into three groups,which are major (utama), intermediate (madya) and contemptible (nista). Some particular Balinese lifestances such as rwa bhineda (dualism), paduwen sareng (common ownership), dan nempahang rage (selfdevotion) enable the different types of ecotourism to live and develop side by side harmonically inBali, without negating each other. Through observation in the micro level, this study found that thecharacteristic of each type tends to shift into hybrid type due to, among others, close interaction withdifferent kinds of stake holders. This also means that the type of ecotourism developed in a village, forexample, will most likely to be modified or improvised in such a way to accommodate the availableresource potency and characteristic of stakeholders involved on its development or management. Theability to manage all forms of ecotourism, which mainly come from outside of Bali, is then combined byBalinese with their life stance of rwa bhineda. Therefore, any ecotourism type or model that comes into,enters and develops in Bali, eventually transforms into a new type of ecotourism.